Reinterpreting the role of primary and secondary airports in low-cost carrier expansion in Europe - Jimenez, Edgar; Suau-Sanchez, Pere (Elsevier, 2020)
This paper discusses the long-term effects of low-cost carrier (LCC) presence at European airports and identifies the airports that have benefited the most from LCC consolidation since 2001. The research uses ‘LCC Market Share’, in terms of seats, to measure the relative importance of LCCs within each airport; and introduces ‘EU LCA Rank’ as a normalised metric of the capacity share of every airport in the European low-cost segment. It evaluates the trends between 2001 and 2019 in all airports in Europe using OAG supply information (seats by carrier). Results show two different phases of LCC rise in Europe, 2001 to 2008 and 2009 to 2019, marked by the effects of the financial crisis of the Great Recession. The analysis highlights the role that LCCs have played in boosting the growth of both primary and secondary airports. Indeed, despite the fact that LCCs have put many smaller airports on the European map, during the second phase of the period of analysis growth has been more significant for major airports and for a few airports that were keen to support the earliest development of LCCs. In that sense, this paper contributes to a better understanding of the historical and contemporary dynamics in European LCCs choice of airports and, in particular, the long-term effects that this disruptive business model have had for airports. This is increasingly important in the context of a potential recovery path from the effects of the response to the Covid-19 pandemic. This paper also attempts to settle academic discussions that attach LCC development to secondary/regional airports disregarding the wide range of strategies used by airlines and airports.
Keywords: Airport dynamics; Low cost airport; Low cost carrier; Airline airport choice